11β-hydroxysteroid dehydrogenase type 1 inhibitor attenuates high-fat diet induced cardiomyopathy. (December 2018) - Huang, Min; Liu, Juan; Sheng, Yunlu; Lv, Yifan; Yu, Jing; Qi, Hanmei; Di, Wenjuan; Lv, Shan; Zhou, Suming; Ding, Guoxian
Abstract: Background: High-fat diet (HFD) induces cardiac hypertrophy; however, the underlying cellular and molecular mechanisms are yet unclear. In the present study, we investigated the roles of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), an amplifier of local glucocorticoid activity, in the pathogenesis of cardiac dysfunction. Methods: Male Wistar rats were fed normal chow diet (NC) or HFD and examined the cardiac remolding and functional alteration by echocardiography and histology. Primary neonatal rat ventricular cardiomyocytes (NRCMs) treated with palmitic acid (PA) or infected by lentivirus were used for identifying the role by 11β-HSD1 in cardiac hypertrophy. Genome microarray of NRCMs was performed to further reveal the mechanism underlying cardiac dysfunction. Results: Palmitic acid induced hypertrophy in NRCMs that upregulated 11β-HSD1 expression in cardiomyocytes, which led to a significant enlargement in the cell size and expression of cardiac hypertrophy-specific genes. Conversely, a remarkable decrease in cardiomyocytes size was detected in either BVT.2733 (a selective inhibitor of 11β-HSD1)-treated or 11β-HSD1-deficient NRCMs. Furthermore, both glucocorticoid receptor (GR) antagonist RU486 and mineralocorticoid receptor (MR) antagonist spironolactone markedly attenuated the 11β-HSD1-induced cardiomyocytes hypertrophy. Genome microarray revealed that cAMP and calcium signaling pathways are potential downstream signaling pathways regulated by 11β-HSD1 in cardiomyocytes hypertrophy. Similar to in vitro results, BVT.2733 strikingly attenuated cardiac hypertrophy and improved cardiac function in HFD-fed rats. Conclusion: 11β-HSD1 acts as an important regulator that controls the cardiac remolding via both GR and MR and the pharmacological inhibition of 11β-HSD1 could be a new therapeutic approach in preventing HFD-induced cardiac hypertrophy. Highlights: 11β-HSD1 plays as an important role in palmitic acid induced cardiac hypertrophy. The cAMP and calcium signaling pathways are regulated by 11β-HSD1 in cardiac hypertrophy. Both GR antagonist and MR antagonist can attenuate palmitic acid induced cardiac hypertrophy. BVT.2733 can attenuate the palmitic acid induced cardiac hypertrophy. BVT.2733 can strikingly improve cardiac function in HFD-fed rats.